Transformative Corporate Social Responsibility and the Circular Economy as a Community-Based Social Work Intervention: Evidence from the WIRALODRA Group in Indonesia - Aaz Anzali; Ezra Divaura Azzahra; Imelda Eka Zulfa; Andromedo Cahyo Purnomo (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2025)
The integration of Corporate Social Responsibility (CSR) and the Circular Economy (CE) has garnered increasing attention as a strategy to address environmental degradation, economic inequality, and social vulnerability in industrial areas. However, many CSR initiatives remain philanthropic in nature and have limited impact on long-term community empowerment. This study examines the implementation of the circular economy as a transformative CSR strategy to enhance community income and capacity, drawing on a case study of the WIRALODRA Group in Indramayu, Indonesia. A qualitative case study approach was employed, with data collected through in-depth interviews with key stakeholders, participant observation, and document analysis. The data were analyzed thematically to capture the dynamics of program implementation and its socio-economic implications. The findings reveal that circular economy practices—such as plastic waste recycling, organic waste processing through Black Soldier Fly (BSF) maggot cultivation, and waste-based product innovation—have facilitated a gradual shift from a linear to a circular waste management system. These practices have generated alternative income sources while strengthening technical skills, social capital, and collective agency among community members. Although income growth remains modest in the short term, the program has fostered social learning processes and enhanced livelihood resilience. This study demonstrates that circular economy–based CSR can function as a form of community-based social work intervention that promotes empowerment, sustainability, and inclusive development in Global South contexts. Keywords: Corporate Social Responsibility, Circular Economy, Community Empowerment, Social Work, Indonesia Integrasi Corporate Social Responsibility (CSR) dan Circular Economy (CE) semakin dipandang sebagai strategi penting dalam menjawab tantangan degradasi lingkungan, ketimpangan ekonomi, dan kerentanan sosial di wilayah sekitar kawasan industri. Namun, sebagian besar praktik CSR masih bersifat filantropis dan belum mampu mendorong pemberdayaan masyarakat secara berkelanjutan. Penelitian ini bertujuan untuk mengkaji implementasi ekonomi sirkular sebagai strategi CSR transformatif dalam meningkatkan pendapatan dan kapasitas komunitas, dengan studi kasus Kelompok WIRALODRA di Indramayu. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara mendalam dengan pemangku kepentingan kunci, observasi partisipatif, dan analisis dokumen, kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa penerapan ekonomi sirkular melalui daur ulang sampah plastik, pengolahan sampah organik berbasis budidaya maggot Black Soldier Fly (BSF), serta inovasi produk berbasis limbah mendorong transformasi sistem pengelolaan sampah dari pola linear menuju sistem sirkular. Praktik ini tidak hanya menciptakan sumber pendapatan alternatif, tetapi juga memperkuat keterampilan teknis, modal sosial, dan agensi kolektif anggota kelompok. Meskipun peningkatan pendapatan belum signifikan dalam jangka pendek, program ini berhasil membangun proses pembelajaran sosial dan ketahanan mata pencaharian komunitas. Studi ini menegaskan bahwa CSR berbasis ekonomi sirkular dapat berfungsi sebagai bentuk intervensi pekerjaan sosial berbasis komunitas yang berorientasi pada pemberdayaan dan keberlanjutan. Kata kunci: corporate social responsibility, ekonomi sirkular, pemberdayaan masyarakat, pekerjaan sosial, Indonesia